Karyological Studies on Six Endemic Plant Taxa in Turkey - Tekin, Mehmet; Gedik, Osman; Kiran, Yasar; Kursat, Murat (Univ Tokyo Cytologia, 2016)
In this study, the chromosome number and detailed morphometric properties of six endemic taxa belonging to five dicot families which grow naturally in Turkey were examined. The somatic chromosome number and karyotype formula of the taxa of Asteraceae family were determined to be 2n=18 and 8m+1sm in Tanacetum argenteum ssp. argenteum and 2n=18 and 7m+2sm+1B in Tanacetum densum ssp. sivasicum, respectively. The somatic chromosome number and karyotype formula were determined as 2n=32 and 10m+6sm in Fumana trisperma belonging to Cistaceae, 2n=14 and 5m+2sm in Onobrychis alblflora belonging to Fabaceae, 2n=14 and 2m+5sm in Salvia blepharochlaena belonging to Lamiaceae, and 2n=14 and 2m+5sm in Glaucium acutidentatum belonging to Papaveraceae family. The somatic chromosome numbers of six taxa collected from different localities in Turkey were counted for the first time, except for T. argenteum var. argenteum and Salvia blepharocleana.
Keywords: Chromosome number; Endemic plant; Karyotype; Sivas; Turkey